A Hardware and Mobile-Health Based System for the Analysis of EEG Signals - Kaya, Turgay; Tuncer, Seda Arslan (My University, 2019)
Instantaneous monitoring of EEG signals is very important for patient follow up. Independent follow-upsystems are needed for the physician to monitor and diagnose the patient continuously. In this article, areal-time design for an FIR (Finite Impulse Response) filter was presented using a cosh window functionimplemented on an FPGA (Field Programmable Gate Array) environment. The reason for using the coshwindow is that it has better ripple ratio and larger sidelobe roll-off ratio than other windows in literature.Since cosh window parameters can be changed in the developed design, they can be easily adapted to thenew state change. After filtering the raw EEG signals, they were converted into a form that could beinterpreted by a specialist physician. The filtered data was uploaded to a server on the internet so that thephysician could access the EEG signals remotely via a mobile phone. The proposed system facilitatedexamination of the patient by the physician and made it possible to help instantly diagnose any illness.
Keywords: Tıbbi İnformatik; Bilgisayar Bilimleri; Yazılım Mühendisliği; Bilgisayar Bilimleri; Bilgi Sistemleri